Study of the effect of the combined drug PN and HA on the regeneration of collagen fibers of the skin in an experiment - Yudin, Mykhailo; Reznik , Anna; Andrusyak , Vita Yevgenievna; Savitskaya, Irina Mikhailovna (Aesthetic Medicine, 2024)
The scientifically justified use of drugs containing polydeoxyribonucleotide (PDRN) to stimulate various regeneration links has been confirmed by repeated publications in the medical literature. The demand for healing medicines in all areas of medicine makes it urgent to search for new effective drugs and their combinations to improve regeneration. The pharmacobiological properties of PDRN and hyaluronic acid (HA) make it clear that in combination these drugs will synergistically stimulate skin healing. However, there is no information about the study of the therapeutic effect of the PDRN/HA combination on the healing of skin wounds yet. In this work, the process of regeneration of collagen fibers (CF) of the skin under the influence of this combination in the preparation TwAc 2.0 was studied on an experimental model of a scalped wound in 17 white mongrel rats. When analyzing the results obtained: macro and microscopic parameters, morphometric parameters of collagen fibers in the field of regeneration, the dynamics of the restoration of the CF of the skin was evaluated and compared in two groups: the study group, where the combined drug PDRN/HA was used, and in the comparison group, where 0.9% NaCl solution was used. Earlier epithelialization of the wound and maturation of the CF, the normotrophic nature of scarring in PDRN/HA group indicates more favorable conditions for regeneration under the influence of the combined drug PDRN/HA.